Penerapan Metode Entropy Dan Metode EDAS Dalam Penerimaan Karyawan Baru Sebagai Pendukung Keputusan - Trenady, Revangga Alif; Mahendra, Rifqi Gusnar; Pungkasanti, Prind Triajeng (Forum Kerjasama Pendidikan Tinggi, 2024)
Selection of new employees is an important thing in a company, because of the variety of criteria that applicants have, so the right method is needed to determine the desired employees. So far, decisions have been made only from a Human Resource Development (HRD) perspective, which sometimes does not match the criteria expected by the company. Therefore, a system is needed to determine the results of new employee selection so that employees are found who meet the criteria expected by the company. This research applies the Entropy and Evaluation methods based on Distance from Average Solution (EDAS) as a decision support system. This research aims to assist companies in making decisions regarding the selection of new employees. The Entropy method is used to determine the weight of each selection criterion, while the EDAS method is applied to evaluate prospective employees. This research was conducted at a spring bed manufacturing company in Semarang by analyzing applicant data which included various criteria such as education, work experience, technical skills, test scores and expected salary. The applicant data sample taken from the company was 15 applicants. From the weighting calculations using the Entropy method and the EDAS method, the result was that Yulius Bagus Caesar had the highest suitability value, namely 1. The research results showed that the combination of Entropy weighting and the EDAS method could simplify the employee selection process based on the expected criteria. Thus, using a combination of Entropy weighting and the EDAS method can be a solution for companies to facilitate the selection of new employees